A dynamic hybrid real-time reconfigurable transmission line simulator (Hardware Component) - Canseco, Roy Vincent L. (2007)
The computer has been a powerful tool for simulation and has replaced most hardware simulators for the power system. However, software simulation is abstract and mathematical in nature. To better understand the behavior of the power system, there is a need to bring out the voltages and currents to physical meters and control devices. This paper documents the hardware component of a dynamic hybrid real-time reconfigurable transmission line simulator. Such a simulator dynamically computes for single-phase transmission line behavior and outputs the result as actual voltage or current waveforms. A micro controller was programmed to receive inputs from a computer. A digital to analog conversion circuit was created convert the output of the micro controller to a corresponding voltage waveform. A buffering and offset removal circuit was built to condition the voltage waveform. A transconductance amplifier was made to convert the voltage waveform to a corresponding current waveform that can drive an overcurrent relay to become active when the program in the computer is simulating a faulted transmission line. Feedback to the micro controller was done to make the computer aware of the state of the relay. This project serves as a key component in developing a micro-controller-based transmission line simulator. It shall be used for the eventual creation of an economical, real-time, and reconfigurable hybrid simulator for large power systems, and for real-time load flow applications.
Thesis (B.S. E.E.)--University of the Philippines Diliman.
Keywords: Electric power systems; Integrated circuits -- Computer simulation; Electric power distribution -- Simulation methods; Transmission line simulator